Metode Isolasi Jamur Patogen Serangga (Aschersonia placenta) Menggunakan Media Water Agar dan Potato Sucrose Agar - RASJMAN, NI MADE SAVITA; SUDIARTA, I PUTU; PHABIOLA, TRISNA AGUNG; WIRYA, GUSTI NGURAH ALIT SUSANTA; SUPUTRA, I PUTU WIRYA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.11, No.2, April 2022, 2022)
Isolation Method of Insect Pathogenic Fungi ( Aschersonia placenta) using Water Agar Media and Potato Sucrose Agar Bali Province is one of the provinces that is famous for its superior agricultural commodities. One of the leading agricultural commodities is citrus. The production of citrus fruits in Bali Province in 2020 is 4,903,341 quintals based on data from the Central Statistics Agency for Bali Province 2021. However, in some citrus-producing areas, citrus fruit production has decreased compared to the previous year. The decline in citrus fruit production is caused by several factors, one of which is the attack of whitefly pests. Whitefly pests can be controlled by utilizing the insect pathogenic fungus Aschersonia placenta . This study aims to determine the isolation method of insect pathogenic fungi Aschersonia placenta using water agar media and potato sucrose agar. The study began with sampling, isolated the fungus and identifying the fungus by morphological characteristics. The results of this study showed that isolation method of A. placenta using water agar media and potato sucrose agar effective for multiply the fungus.